GPR41 and GPR43 in Obesity and Inflammation – Protective or Causative? - Ang, Zhiwei; Ding, Jeak Ling (Frontiers in Immunology, 2016)
GPR41 and GPR43 are a pair of mammalian G-protein coupled receptors (GPCRs) expressed in human adipocytes, colon epithelial cells and peripheral blood mononuclear cells. These receptors are activated by short-chain fatty acids (SCFAs) such as acetate, propionate and butyrate– which are produced during dietary fiber fermentation by resident gut bacteria. This unique ligand specificity suggests that GPR41 and GPR43 may mediate the interaction between the human host and the gut microbiome. Indeed, studies on knockout mice implicate GPR41 and GPR43 in chronic inflammatory disorders such as obesity, colitis, asthma and arthritis. However, whether GPR41 and GPR43 are protective or causative is inconsistent between studies. This discrepancy may be due to differences in the disease models used, the inbred mouse strains or non-specific knockout effects. Here, we review the latest findings on GPR41 and GPR43, highlighting contradictory observations. With GPR41 and GPR43 being considered as drug targets, it is pertinent that their role is fully elucidated. We propose that future studies on human tissues, ex vivo, may allow us to confirm the role of GPR41 and GPR43 in humans, be it protective or causative.